THE CHRONICLES OF THE PRESS OF THE REPUBLIC OF UZBEKISTAN AND THE REGIONS KEEP PACE WITH THE TIMES - Yakubova Nodira Tulaganovna (American Journals Publishing, 2024)
This article explores the processes of historical development of the press of the Republic of Uzbekistan and the region and analyzes the impact of the modern Press on social, political and cultural life. The role of the press in society, its role in obtaining and disseminating information, as well as its harmonization with modern technologies, are detailed. The article also provides information about the development of the regional press and its importance in regional issues.
Keywords: Press of Uzbekistan, Regional press, Information, Modern technologies, social life, Political life, Cultural life, History of development.